2015
DOI: 10.1177/1357633x15583215
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the use of telehealth in speech, language and hearing sciences

Abstract: The advancement of information and communication technologies provides more favourable conditions for providing distance care in several areas. Most of studies concluded that the telehealth procedure had advantages over the non-telehealth alternative approach (85.5%); however, 13.6% reported that it was unclear whether the telehealth procedure had advantages. Some barriers still need to be overcome, such as technology, training, regulation, acceptance and recognition of the benefits of this practice by the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
159
1
20

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(197 citation statements)
references
References 104 publications
17
159
1
20
Order By: Relevance
“…Telehealth is finding increasingly wide application among speech-language pathologists (SLPs) 16 . Its capacity to improve service access, efficiencies and outcomes for an expanding range of difficulties, disorders and populations is well supported by research 17 .…”
Section: Technology As Part Of a Solution To Allied Health Accessmentioning
confidence: 99%
“…Telehealth is finding increasingly wide application among speech-language pathologists (SLPs) 16 . Its capacity to improve service access, efficiencies and outcomes for an expanding range of difficulties, disorders and populations is well supported by research 17 .…”
Section: Technology As Part Of a Solution To Allied Health Accessmentioning
confidence: 99%
“…In terms of telehealth in the area of Speech Therapy and Audiology, a prevalence of publications in the area of Audiology, with greater focus on assessment or intervention, has been observed, and the number of papers on this subject has risen, mainly in the last five years 12 . Correlating telehealth in speech and language pathology and audiology, inserted into the contemporary marketing and compared to the condition of product or service, it can be made available to users, provided that studies examining its quality and facilitating the sustainability of such actions with optimization strategies for its operation, be carried out 13 .…”
mentioning
confidence: 99%
“…Some children will present with normal skills, and will not require a comprehensive assessment. This may improve efficiency and save costs for the service provider (32 Telepractice also offers the opportunity for local SLPs to access educational and mentoring opportunities (131,(138)(139)(140). Telemedicine studies have reported improved communication between local doctors and paediatric subspecialists (138,139,141), with subsequent improvements in the quality and continuity of care (138,139,(141)(142)(143)(144)(145).…”
Section: Figure 6 Possible Telepractice Screening Pathwaymentioning
confidence: 99%
“…These studies report that SLPs are often reluctant to provide direct services due to concerns regarding the efficacy of assessment and therapy interventions delivered via telepractice. It is interesting that this perception continues despite a growing evidence base in the area of speech pathology telepractice (32,(147)(148)(149)(150)(151)(152)(153)(154)(155)(156)(157)(158)(159)(160)(161).…”
Section: Suitability Of Patient Groups and Services For Telepracticementioning
confidence: 99%
See 1 more Smart Citation